SEZs and China’s Development Promotion: Policy Exchanges Under the Belt and Road Initiative - Rodrigues, Carlos (2021)
RODRIGUES, Carlos; STEENHAGEN, Pedro. SEZs and China’s Development Promotion: Policy Exchanges Under the Belt and Road Initiative. In: FIGUEIREDO, Paulo; LEANDRO, Francisco José; LI, Yichao. Handbook of Research on Special Economic Zones as Regional Development Enablers. Hershey: IGI Global, 2021.